Heterogeneity in resistant fecal Bacteroides fragilis group collected from healthy people. (June 2016) - Narimani, T.; Douraghi, M.; Owlia, P.; Rastegar, A.; Esghaei, M.; Nasr, B.; Talebi, M.
Abstract: Normal nonpathogenic flora would represent a constant lake of resistance genes potentially transferable to human pathogens. To assess the prevalence of resistance genes and genetic variability of Bacteroides fragilis group (BFG) from normal flora, 177 Bacteroides isolates obtained from the fecal samples of healthy individuals. These isolates were subjected to antibiotic susceptibility testing and pulsed field gel electrophoresis (PFGE). The isolates were further tested for the presence of erm F, tet Q and bft genes by PCR. Our results indicated the presence of different clonal strains (1 common type and 57 single types) among the resistant isolates. The resistance rate for the six antibiotics in this study was between 1% and 95%. Most of the isolates (99%) were susceptible to metronidazole. erm F and tet Q were detected in all erythromycin and tetracycline resistant isolates. None of the isolates were carried bft gene. These data suggest dissemination of heterogenic clonal groups in healthy persons and resistance to 5 high commonly used antibiotics.